PENINGKATAN PROFESIONAL GURU MELALUI KOMUNIKASI INFORMAL - Sri Handayani (Sekolah Dasar: Kajian Teori dan Praktik Pendidikan, 2017)
Abstract: The study was aimed at describing (1) the process and the components of informal communication in improving the teachers’ professionalism, and (2) the informal communication model in improving the professionalism of elementary school teachers in Jember Regency. The research method used was qualitative with phenomenological approach which was multi-site study on three elementary schools. The data was collected by interviewing, observing, and documenting. The data analysis was carried out by using flow and constant comparative models. The results showed the improvement of the teachers’ professionalism through the process and the components of informal communication including cognitive, affective, and psychomotor aspects. The informal communication model in improving the teachers’ professionalism on this case (1) was in the form of direct interactive model, (2) was in the form of indirect interactive model, and case (3) was in the form of direct and indirect interactive model.